Faktor Penentu Loyalitas Pelanggan Skincare di Indonesia: Tinjauan Literatur Semi-Sistematis dan Pengembangan Model Hierarki - Lestari, Dinda Dwi; Mihardja, Eli Jamilah (VISA: Journal of Vision and Ideas, 2025)
Indonesia’s skincare industry is growing rapidly (4.6% per year), but is faced with intense competition and a high risk of brand switching. This research was conducted to answer the urgency of understanding the dynamics of customer loyalty in this context. The objectives of this study are to identify the determinants of loyalty, including the role of culture (such as halal certification), and develop a loyalty hierarchy model. This research used the method of semi-systematic literature review from three databases (Scopus, Taylor & Francis, and Google Scholar) resulting in 22 selected journal articles (2021-2025). The results showed that cultural factors (halal certification) are significant in religious areas (such as Central Java) but not in metropolitan areas such as Jabodetabek. Five predictors consistently shape skincare loyalty: brand image, perceived value, brand experience, customer satisfaction, and brand love. The main contribution of this research is the development of an integrative model based on Oliver’s (1999) loyalty hierarchy. This model accommodates the five predictors from empirical research and adds the role of social media as a crucial marketing medium. As a result, this model offers a strategic roadmap for industry players to build sustainable loyalty as well as future research opportunities.